Identification of JAMU KU-HE-SE as an Alternative Health Supporting Ingredient - Botahala, Loth; Djasibani, Hemy Ratmas; Karbeka, Martasiana; Nahak, Maria Hendriana (Biology, Medicine, & Natural Product Chemistry, 2025)
Herbal plants have been used since ancient times in traditional medicine and continue to be maintained and preserved in Indonesia. They are called Jm. Each part of an herbal plant has active components in the form of secondary metabolite compounds, ranging from tubers, wood, sap, latex, leaves, flowers, fruits, and seeds that function to maintain life in their environment. Turmeric, ginger, and lemongrass are included in Jm plants, which are very useful in traditional medicine because they have various secondary metabolite compounds. This study aims to obtain an even distribution of secondary metabolite compounds through phytochemical tests, inhibition of free radicals through antioxidant activity tests, and an even distribution of nutrients through proximate analysis in JKHS samples with a certain formula. The results of the phytochemical test showed that JKHS contains several important phytochemical components with the intensity it shows. Phenolic content (++) can provide benefits in protecting body cells from oxidative damage. Saponin (+) has anti-inflammatory properties and has the potential as an antimicrobial agent. In addition, steroids (+) and terpenoids (++), play a role in regulating the body's physiological functions and can support hormonal balance and the immune system and the potential in treating certain diseases. Alkaloid content (+)can affect the nervous system and has analgesic and stimulant properties. JKHS samples also contain carotenoids (+), which protect body cells from free radicals and oxidative damage. With the  value of 4.838 µg / mL of the sample, it shows that JKHS extract has very strong antioxidant potential. Through proximate analysis, it was obtained that the water content (15.38%) reflects the humidity level in JKHS which can affect the stability of product storage, the ash content (6.29%) indicates that JKHS can be a good source of minerals to support health, the crude protein content (3.79%) indicates that JKHS contributes to daily protein intake, especially in regular consumption, the fat content (6.43%) contributes energy and plays an important role in the absorption of fat-soluble vitamins and other bioactive compounds that may be contained in JKHS, the carbohydrate content (81.37%) indicates that the main component of JKHS is carbohydrates, which function as the main source of energy for the body that can support physical activity and daily energy needs, and the fiber content (5.45%) is an important component that helps smooth the digestion process, improves intestinal health, and helps prevent digestive disorders such as constipation, and plays a role in maintaining blood sugar levels and supporting weight management. Overall, the proximate composition of JKHS has good nutritional value, with carbohydrates as the dominant energy source, as well as additional protein, fat, and fiber that support overall health. This combination of formulas makes JKHS have great potential as a Jm drink that can provide various health benefits, especially in protecting the body from oxidative stress, inflammation, and other disease risks, including supporting the regeneration of cells, nerves, and other organs of the body that are weak due to climate, work, or old age.